ASSOCIATION BETWEEN SERUM URIC ACID AND METABOLIC SYNDROME COMPONENTS AT TERTIARY CARE HOSPITAL, NORTH WEST RAJASTHAN - YADAV, POOJA; VYAS, SWATI; RP, AGRAWAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The term “metabolic syndrome” (MetS) refers to a concept rather than a specific illness. All cardiovascular events seen in participants cannot be explained by the established risk factors for metabolic syndrome. We investigated the relationship between uric acid levels and the different elements of the metabolic syndrome. Methods: The Department of Medicine, S.P. Medical College, Bikaner, Rajasthan, conducted a case control study from January 2020 to December 2020 on 150 cases of metabolic syndrome as per NCEP ATP III definition criteria and harmonizing definition criteria, admitted in various wards, and 150 healthy individuals taken as controls selected by simple random sampling and matched for confounding factors. Results: Both the study group and the control group had comparable socio-demographics. In the metabolic group (study group), the prevalence of hyperuricemia was 20% with a mean of 6.00±0.98 mg/dL, compared to 22.3% in men and 16.07% in women. When the maximal number of metabolic syndrome components (4 or 5) were present, the mean blood uric acid level was 6.4 1.03 mg/dL (p = 0.001). Conclusion: The incidence of the metabolic syndrome and its elements was substantially correlated with serum uric acid levels.